Analysis Of The Influence Of Product Quality, Price Perceptions, And Location Strategies And Services On Rantauprapat Clothing - Panjaitan, Ahmad Padlan; Simanjorang, Elida Florentina Sinaga; Syahputra, Rizki (International Journal of Science, Technology & Management, 2022)
This study aims to determine the effect of product quality, price perception and location and service strategies on clothing purchasing decisions at Raza Distro Rantauprapat. The population in this study were all consumers of Raza Distro Rantauprapat who had decided to buy clothes at Raza Distro. The sample used in this study was taken as many as 100 respondents using a non-probability sampling technique with an accidental sampling approach. The analytical method used is multiple linear regression analysis. The results of this study using the regression equation formed are Y = 14.054 + 0.105X1 + 0.419X2 + 0.308X3 + 0.342X4, which means that price perception has the greatest influence compared to three other independent variables such as product quality, location strategy, and service. Overall, the results of this study indicate that the variables of product quality, price perception, location, and service strategies have a positive and significant impact on clothing purchasing decisions at Raza Distro Rantauprapat.